2022
DOI: 10.3390/molecules27175544
|View full text |Cite
|
Sign up to set email alerts
|

Residue and Risk Assessment of Fluopyram in Carrot Tissues

Abstract: This study describes the variation in residue behavior of fluopyram in soil, carrot root, and carrot leaf samples after the application of fluopyram (41.7% suspension, Bayer) by foliar spray or root irrigation at the standard of 250.00 g active ingredient per hectare (a.i./ha) and double-dose treatment (500.00 g a.i./ha). Fluopyram and its metabolite fluopyram-benzamide were extracted and cleaned up using the QuEChERS method and subsequently quantified with LC-QQQ-MS/MS. The LOD and LOQ of the developed method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…The HQc and HQa values of total FLU and TRI ranged from 0.0010 to 0.099 and 0.0027 to 0.057, respectively, although the highest value was still far smaller than 1, indicating low risks of adverse effects following exposure to FLU and TRI based on the results of the present study. Similarly, previous studies also revealed a low dietary risk of exposure to FLU or TRI from various agricultural products, such as onions, carrots, strawberries and mangoes [12,[39][40][41]. The risks associated with exposure to FLU and TRI should not be ignored.…”
Section: Discussionmentioning
confidence: 84%
“…The HQc and HQa values of total FLU and TRI ranged from 0.0010 to 0.099 and 0.0027 to 0.057, respectively, although the highest value was still far smaller than 1, indicating low risks of adverse effects following exposure to FLU and TRI based on the results of the present study. Similarly, previous studies also revealed a low dietary risk of exposure to FLU or TRI from various agricultural products, such as onions, carrots, strawberries and mangoes [12,[39][40][41]. The risks associated with exposure to FLU and TRI should not be ignored.…”
Section: Discussionmentioning
confidence: 84%